Ex vivo Ikkβ ablation rescues the immunopotency of mesenchymal stromal cells from diabetics with advanced atherosclerosis. Issue 3 (1st July 2020) - Kizilay Mancini, Ozge; Huynh, David N; Menard, Liliane; Shum-Tim, Dominique; Ong, Huy; Marleau, Sylvie; Colmegna, Ines; Servant, Marc J
Abstract: Aims: Diabetes is a conventional risk factor for atherosclerotic cardiovascular disease and myocardial infarction (MI) is the most common cause of death among these patients. Mesenchymal stromal cells (MSCs) in patients with type 2 diabetes mellitus (T2DM) and atherosclerosis have impaired ability to suppress activated T-cells (i.e. reduced immunopotency). This is mediated by an inflammatory shift in MSC-secreted soluble factors (i.e. pro-inflammatory secretome) and can contribute to the reduced therapeutic effects of autologous T2DM and atherosclerosis-MSC post-MI. The signalling pathways driving the altered secretome of atherosclerosis- and T2DM-MSC are unknown. Specifically, the effect of IκB kinase β (IKKβ) modulation, a key regulator of inflammatory responses, on the immunopotency of MSCs from T2DM patients with advanced atherosclerosis has not been studied. Methods and results: MSCs were isolated from adipose tissue obtained from patients with (i) atherosclerosis and T2DM (atherosclerosis+T2DM MSCs, n = 17) and (ii) atherosclerosis without T2DM (atherosclerosis MSCs, n = 17). MSCs from atherosclerosis+T2DM individuals displayed an inflammatory senescent phenotype and constitutively expressed active forms of effectors of the canonical IKKβ nuclear factor-κB transcription factors inflammatory pathway. Importantly, this constitutive pro-inflammatory IKKβ signature resulted in an altered secretome and impaired in vitro immunopotency and in vivo healing capacity in an acute MI model. Notably, treatment with a selective IKKβ inhibitor or IKKβ knockdown (KD) (clustered regularly interspaced short palindromic repeats/Cas9-mediated IKKβ KD) in atherosclerosis+T2DM MSCs reduced the production of pro-inflammatory secretome, increased survival, and rescued their immunopotency both in vitro and in vivo. Conclusions: Constitutively active IKKβ reduces the immunopotency of atherosclerosis+T2DM MSC by changing their secretome composition. Modulation of IKKβ in atherosclerosis+T2DM MSCs enhances their myocardial repair ability. Graphical Abstract: